Difference in the Vitreal Protein Profiles of Patients with Proliferative Diabetic Retinopathy with and without Intravitreal Conbercept Injection - Chen Zou; Minjie Zhao; Jingjing Yu; Dandan Zhu; Yunzhi Wang; Xinping She; Yanan Hu; Zhi Zheng (Journal of Ophthalmology)
Purpose. To examine the difference in the vitreal protein profiles of patients with proliferative diabetic retinopathy (PDR) with and without preoperative intravitreal conbercept (IVC) treatment. Methods. Liquid chromatography-tandem mass spectrometry- (LC-MS/MS-) based proteomic methods were used to determine the protein profiles of the vitreous humor in patients with PDR treated with (IVC group; n=9) and without (PDR group; n=8) preoperative IVC. Gene ontology (GO) annotation and REACTOME pathway analysis were obtained to overview differentially expressed proteins between each group. Intravitreal levels of apolipoprotein A-II (APOA2) and ceruloplasmin (CP) were measured using enzyme-linked immunosorbent assays. Results. 307 proteins were expressed differentially between PDR and IVC groups, including 218 proteins downregulated in response to IVC. The most notable GO annotations in level 3 and REACTOME pathways describing the differentially expressed proteins were “innate immune response” and “platelet degranulation.” The intravitreal levels of APOA2 and CP were lower in the IVC group than in the PDR group (p<0.01). Conclusions. In addition to decreasing the intravitreal vascular endothelial growth factor level, IVC may alter the vitreal protein profile in patients with PDR, with the differentially regulated proteins involved in the immune response, platelet degranulation, complement activation, and inflammation.